Mentorship: An international perspective - Fulton, John; Bøhler, Ann; Hansen, Grethe Storm; Kauffeldt, Anders; Welander, Eva; Santos, Margarida Reis; Thorarinsdottir, Kristin; Ziarko, Ewa (Nurse Education in Practice, 2007)
This paper is an account of a project funded by the European Union as a Leonardo da Vinici pilot project which aimed to produce a framework for a programme which prepares qualified nurses for their role as mentor of the student nurse. Representatives from universities in Norway, Sweden, Iceland, Poland, Portugal and the United Kingdom were the partner countries. The project was developed through the establishment of a series of common meetings sequentially held in each of the partner countries. The aim of these meetings was to devise a common curriculum for the preparation of mentors of students, when in practice, thereby sharing views, experiences and expectations. Initially, the group established a common philosophy specifically theory and practice were seen as a single entity with theory being both related to and drawn from practice. Reflection and reflection on practice was also seen as important; an inductive model which emphasized the dialectical relationship between theory (abstract thinking), practice (concrete experiences), reflected observation (induction) and active experimentation (deduction) and serve to reduce the gap between theory and practice. The process evolved rather than was a predetermined plan but on reflection the process involved several stages: the first lay in the identification of a common understanding of terms and a shared common philosophy. A framework is then devised which allows the partner countries to develop their programme according to local and national needs.